Analysis of gene expression dynamics revealed delayed and abnormal epidermal repair process in aged compared to young skin - Sextius, Peggy (Arch Dermatol Res, 2015)
With aging, epidermal homeostasis and barrier function are disrupted. In a previous study, we analyzed the transcriptomic response of young skin epidermis after stratum corneum removal, and obtained a global kinetic view of the molecular processes involved in barrier function recovery. In the present study, the same analysis was performed in aged skin in order to better understand the defects which occur with aging. Thirty healthy male volunteers (67 ± 4 years old) were involved. Tape-strippings were carried out on the inner face of one forearm, the other unstripped forearm serving as control. At 2, 6, 18, 30 and 72 h after stripping, TEWL measurements were taken, and epidermis samples were collected. Total RNA was extracted and analyzed using DermArray(®) cDNA microarrays. The results highlighted that barrier function recovery and overall kinetics of gene expression were delayed following stripping in aged skin. Indeed, the TEWL measurements showed that barrier recovery in the young group appeared to be dramatically significant during the overall kinetics, while there were no significant evolution in the aged group until 30 h. Moreover, gene expression analysis revealed that the number of modulated genes following tape stripping increased as a function of time and reached a peak at 6 h after tape stripping in young skin, while it was at 30 h in aged skin, showing that cellular activity linked to the repair process may be engaged earlier in young epidermis than in aged epidermis. A total of 370 genes were modulated in the young group. In the aged group, 382 genes were modulated, whose 184 were also modulated in the young group. Only eight genes that were modulated in both groups were significantly differently modulated. The characterization of these genes into 15 functional families helped to draw a scenario for the aging process affecting epidermal repair capacity.